2007
DOI: 10.1016/j.biomaterials.2007.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface wettability and contact time on protein adhesion to biomaterial surfaces

Abstract: Atomic force microscopy (AFM) was used to directly measure the adhesion forces between three test proteins and low density polyethylene (LDPE) surfaces treated by glow discharge plasma to yield various levels of water wettability. The adhesion of proteins to the LDPE substrates showed a step dependence on the wettability of surfaces as measured by the water contact angle (θ). For LDPE surfaces with θ > ∼60-65°, stronger adhesion forces were observed for bovine serum albumin, fibrinogen and human FXII than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
440
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(478 citation statements)
references
References 52 publications
31
440
0
7
Order By: Relevance
“…It has been shown that low cell adhesion strength is related to the dispersive component of SFE [21]. Previous works also demonstrated that: the more hydrophilic the material the more cells will adhere on the surface [22,23]. In this study both groups of scaffolds (β-TCP and BCP) presented a larger polar component compared to the apolar one.…”
Section: Discussionmentioning
confidence: 50%
“…It has been shown that low cell adhesion strength is related to the dispersive component of SFE [21]. Previous works also demonstrated that: the more hydrophilic the material the more cells will adhere on the surface [22,23]. In this study both groups of scaffolds (β-TCP and BCP) presented a larger polar component compared to the apolar one.…”
Section: Discussionmentioning
confidence: 50%
“…Protein adsorption is influenced by the particular physico-chemical properties of the biomaterial surface which include chemistry, wettability; charge, and surface morphology [8]. The wettability of a material surface is considered to be one of the most influential parameters affecting protein adsorption with numerous studies in particular investigating protein adsorption and cellular adhesion on surfaces with a designed wettability gradient [9][10][11][12]. It is generally considered that proteins tend to adsorb more favourably onto hydrophobic than hydrophilic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that proteins tend to adsorb more favourably onto hydrophobic than hydrophilic surfaces. Both Lee [13] and Xu [12] treated polyethylene material with a glow discharge plasma to produce surfaces with a wettability gradient for the study of albumin and fibrinogen (Fg) adsorption. These studies showed an increased amount of protein adsorption on hydrophobic surfaces and in the latter case, higher protein adhesion forces as surface hydrophobicity increased.…”
Section: Introductionmentioning
confidence: 99%
“…A-type carbonate apatite, corresponding to a location of carbonate ions at monovalent anionic OH -sites, had lower wettability, lower cell spreading, and similar cell proliferation compared with HA. Surface wettability on several biomaterials other than apatite affects cell adhesion on polymer 16 , glass microscope slides 17 , yttria partially stabilized zirconia 18 , poly (methyl methacrylate) 13 , and titanium 14,19 . Despite the differences in substrates or methods for the improvement of surface wettability, changes in the surface wettability of biomaterials brought out advantages in cellular behaviors such as attachment and spreading.…”
Section: Discussionmentioning
confidence: 99%